ANALISIS PENGENDALIAN INTERNAL TERHADAP PENJUALAN PADA PT. GROWTH ASIA - Farida Sagala; Arthur Simanjuntak; Lamria Sagala; Mitha Christina Ginting (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
The purpose of this research is to find out how the implementation of internal sales control runs effectively and efficiently. Claims internal control is very important so that claims are received on time. PT. Growth Asia is a foundry company. Documentation and interviews are used as data collection methods. The research method used in this research is narrative qualitative. Analytical technology uses data reduction techniques, data visualization, and data verification. The results of the study show that internal component controls in sales control are effective because internal component controls already exist within the company and credit limits apply. The results of this study also indicate that internal control over receivables is quite effective in terms of a clear division of labor, where more than one department handles receivable collection. sales level of PT. Asia's growth accelerated from 2020-2021, demonstrating that internal sales controls are working effectively.